2014
DOI: 10.1080/19415257.2014.940628
|View full text |Cite
|
Sign up to set email alerts
|

Motivation as critical factor for teacher development in contextually challenging underperforming schools in South Africa

Abstract: There is considerable interest in teacher development at present. This is especially so at underperforming schools, where teacher development is seen as an essential ingredient in transforming these schools into performing schools. Since many teachers at these schools might be reluctant to participate in development activities, it is important to identify the factors that might motivate them to do so. This article first surveys the literature on aspects of motivation, professional development and adult learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 24 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…Our findings suggest that teachers' willingness to improve their classroom interactions with students is based on their professional needs as well as opportunities to learn. This finding is in line with recent research on teachers' motivation to learn (Heystek & Terhoven, 2015;McMillan, McConnell, & O'Sullivan, 2016). This work contributes to an emergent understanding of teachers' motivations to develop classroom interaction knowledge in the workplace.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings suggest that teachers' willingness to improve their classroom interactions with students is based on their professional needs as well as opportunities to learn. This finding is in line with recent research on teachers' motivation to learn (Heystek & Terhoven, 2015;McMillan, McConnell, & O'Sullivan, 2016). This work contributes to an emergent understanding of teachers' motivations to develop classroom interaction knowledge in the workplace.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, Ch7 (Inadequate professional development, 83.2%) ranks second in the challenge list as a major hindrance for school improvement. As a school leader, the principal must have the foresight for effective, efficient, and dynamic principles in handling matters between the school, staff, and the host community, it is only possible by adequate and continuous professional growth and advancement (Chu & Cravens, 2012;Heystek & Terhoven, 2015).…”
Section: Figure 3: Frequency Analysismentioning
confidence: 99%
“…Accordingly, all difficulties must be minimized, so the learner outcome should be at the ultimate possible level (Bush & Glover, 2016;Mazzeo, 2003). Inevitably, the school principal position now is demanding, highly complex, changing, and dynamic, which requires strategic approaches to transform low-performing schools into defensible betterment among students (Heystek & Terhoven, 2015;Holmes, Clement, & Albright, 2013). The basic approaches are managing the instructional program, maintaining, and developing staff, redesigning the school organization, setting directions, and improving school culture to maximize organizational effectiveness and student improvement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Malawi found that poor allowances received during training as well as poor conditions of service contributed to a lack of motivation among teachers to bring new practices into their classrooms (Selemani-Meke, 2013). In contrast, in South Africa, teachers from underperforming schools were motivated to engage in professional development activities based on a passion for working with children from disadvantaged backgrounds, acknowledgment from school leaders, the approach used to inform teachers of development activities, feelings of empowerment after learning new strategies, and the style of the presenters delivering the training (Heystek & Terhoven, 2014). Properly designed professional development activities, therefore, can increase teacher motivation to participate and use new strategies learned.…”
Section: Teacher Motivation In Low-and Middle-income Countriesmentioning
confidence: 99%